Designing Board Games as an Enhancer of A Sense of Community and Cognition for The Elderly of Tresna Werdha Budi Pertiwi Social Care - Amaliani, Ragil Nahya; Soewardikoen, Didit Widiatmoko; Azhar, Hanif; Rahman, Yanuar (Sahabat Publikasi, 2025)
The elderly population often experiences a decline in social interaction and cognitive function, especially in institutional settings such as the Tresna Werdha Budi Pertiwi Social Home in Bandung. Residents frequently face isolation and reduced mental stimulation, which impairs their emotional well-being and independence. This study aims to design a board game that enhances social togetherness and improves cognitive ability among older women in the institution. Using a Design Thinking methodology, researchers engaged in five stages: empathize (through interviews and observations), define (via SWOT analysis and crossover), ideate (sketching concepts and mind mapping), prototype (creating physical mock-ups), and test (evaluating usability with real users). The final product, titled